Psychotic traits in comedians. (May 2014) - Ando, Victoria; Claridge, Gordon; Clark, Ken
Abstract : Background: The popular belief that creativity is associated with madness has increasingly become the focus of research for many psychologists and psychiatrists. However, despite being prime examples of creative thinking, comedy and humour have been largely neglected. Aims: To test the hypothesis that comedians would resemble other creative individuals in showing a higher level of psychotic characteristics related to both schizophrenia and manic depression. Method: A group of comedians ( n =500+) and a control sample of actors ( n = 350+) completed an online questionnaire containing the short version of the Oxford–Liverpool Inventory of Feelings and Experiences (O-LIFE), with scales measuring four dimensions of psychotic traits. Scores were compared with general population norms. Results: Comedians scored significantly above O-LIFE norms on all four scales. Actors also differed from the norms but on only three of the scales. Most striking was the comedians' high score on both introverted anhedonia and extraverted impulsiveness. Conclusions: This unusual personality structure may help to explain the facility for comedic performance.